Molecular dynamics simulations of transitions for ECD epidermal growth factor receptors show key differences between human and drosophila forms of the receptors. Issue 7 (10th April 2013) - Perilla, Juan R.; Leahy, Daniel J.; Woolf, Thomas B.
<x xml:space="preserve">Abstract</x> Recent X‐ray structural work on the Drosophila epidermal growth factor receptor (EFGR) has suggested an asymmetric dimer that rationalizes binding affinity measurements that go back decades (Alvarado et al., Cell 2010;142:568–579; Dawson et al., Structure 2007;15:942–954; Lemmon et al., Embo J 1997;16:281–294; Mattoon et al., Proc Natl Acad Sci USA 2004;101:923–928; Mayawala et al., Febs Lett 2005;579:3043–3047; Ozcan et al., Proc Natl Acad Sci USA 2006;103:5735–5740). This type of asymmetric structure has not been seen for the human EGF receptor family and it may or may not be important for function in that realm. We hypothesize that conformational changes in the Drosophila system have been optimized for the transition, whereas the barrier for the same transition is much higher in the human forms. To address our hypothesis we perform dynamic importance sampling (DIMS) (Perilla et al., J Comput Chem 2010;32:196–209) for barrier crossing transitions in both Drosophila and human EFGRs. For each set of transitions, we work from the hypothesis, based on results from the AdK system, that salt‐bridge pairs making and breaking connections are central to the conformational change. To evaluate the effectiveness of the salt‐bridges as drivers for the conformational change, we use the effective transfer entropy based on stable state MD calculations (Kamberaj and Der Vaart, Biophys J 2009;97:1747–1755) to define a reduced subset of degrees of freedom that seem to be important for driving the transition (Perilla and Woolf, J Chem Phys 2012;136:164101). Our results suggest that salt‐bridge making and breaking is not the dominant factor in driving the symmetric to asymmetric transition, but that instead it is a result of more concerted and correlated functional motions within a subset of the dimer structures. Furthermore, the analysis suggests that the set of residues involved in the transitions from the Drosophila relative to the human forms differs and that this difference in substate distributions relates to why the asymmetric form may be more common to Drosophila than to the human forms. We close with a discussion about the residues that may be changed in the human and the Drosophila forms to potentially shift the kinetics of the symmetric to asymmetric transition. Proteins 2013; 81:1113–1126. © 2013 Wiley Periodicals, Inc.